High-accuracy polarization measurements of the white-light corona during the 2023 total solar eclipse - Hanaoka, Yoichiro; Sakai, Yoshiaki; Masuda, Yukio (Frontiers in Astronomy and Space Sciences, 2024)
This study measured the polarization of the white-light corona during the total solar eclipse on 20 April 2023, which occurred under high solar activity. The same instrument that was used for the 2017 and 2019 eclipse observations was employed, and despite the short duration of totality, the obtained data could be used for high-accuracy polarization analysis. We derived the brightness and polarization of the K + F corona and estimated the brightness distributions of the K- and F-coronae using polarization information. The polarization data of the corona are the key to estimating the amount of coronal hot plasma and its electron density distribution. Therefore, we examined the consistency between the eclipse data and those taken by the C2 coronagraph of the Large Angle Spectrometric Coronagraph (LASCO) on board the Solar and Heliospheric Observatory. Consequently, a systematic difference was observed; the polarization measured by LASCO-C2 was approximately 30% smaller than the results from the eclipse. Data from eclipses, which are captured under low background sky brightness and no scattered light due to the Sun’s disk, can be a good calibration source of the brightness and polarization of the white-light corona.